Capital is key: a case for migrants' cultural capital. (2018) - Echa, P.I.
In this paper, I argue that possession and utilisation of capital are at the centre of migrants' success and the ability to thrive in their new environment. Pierre Bourdieu's 'Forms of Capital' serve as a starting point in this research. While Bourdieu's capital accounts for the structuring of the social world completely, this article concentrates on migrants' experiences in the Netherlands. This article shows how Bourdieu's concept of capital illustrates how migrants' capital brought from their home countries becomes a source of power, as well as the difference(s) between just surviving in their new environment and thriving. Ethnographic research, published works on the subject of the appropriation of capital by migrants, and statistical accounts in the Netherlands are used. These sources illustrate that migrants face challenging circumstances in the Netherlands due to discrimination, racism and lack of capital. I show how West African musicians thrive amidst these challenges through the possession of cultural capital (e.g., musical skills).